Complete mitochondrial genome of the common cutworm Spodoptera litura (Lepidoptera: Noctuidae). (2nd November 2015) - Li, Feng-Bo; Zhang, Hui-Xian; Shen, Wei-Feng; Xu, Xiao-Yan; Wang, Wei; Chen, Jin-E; He, Li-Hua; Meng, Zhi-Qi
Abstract: We determined the complete mitochondrial genome of the common cutworm Spodoptera litura (Lepidoptera: Noctuidae), which is one of the most destructive polyphagous insect pests worldwide. The genome is 15, 383 bp in length (GenBank accession number: KF701043) with an A + T content of 81.08%, and contains 37 typical animal mitochondrial genes (13 protein-coding genes, 2 rRNA genes and 22 tRNA genes) with the typical arrangement found in Lepidoptera. All the protein-coding genes (PCGs) start with ATN start codon except for cox1, which begins with CGA. Eight PCGs stop with complete termination codons (TAA or TAG), whereas five PCGs use incomplete stop codon T. The A + T-rich region is located between rrnS and trnM with a length of 326 bp and an A + T content of 93.87%, and harbors three tandem repeat elements.